2017
DOI: 10.1093/mnrasl/slx093
|View full text |Cite
|
Sign up to set email alerts
|

On the galaxy–halo connection in the EAGLE simulation

Abstract: Empirical models of galaxy formation require assumptions about the correlations between galaxy and halo properties. These may be calibrated against observations or inferred from physical models such as hydrodynamical simulations. In this Letter, we use the EAGLE simulation to investigate the correlation of galaxy size with halo properties. We motivate this analysis by noting that the common assumption of angular momentum partition between baryons and dark matter in rotationally supported galaxies overpredicts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 45 publications
10
31
3
Order By: Relevance
“…• The halo properties we explore -including spin and concentration -do not reduce the scatter in the GHSR in our sample of low-mass, dispersion supported galaxies in FIREbox. Our weak dependence on spin disagrees with classical theoretical ideas of galaxy formation (Mo et al 1998), but agrees with recent numerical works of more massive galaxies (Desmond et al 2017;Garrison-Kimmel et al 2018;Jiang et al 2019). At a fixed halo size, the weak correlation of galaxy sizes with halo spin and concentration agree with FIRE-2 zoom simulations (Garrison-Kimmel et al 2018) and semi-empirical models (Zanisi et al 2020(Zanisi et al , 2021a of more massive, rotationally supported galaxies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…• The halo properties we explore -including spin and concentration -do not reduce the scatter in the GHSR in our sample of low-mass, dispersion supported galaxies in FIREbox. Our weak dependence on spin disagrees with classical theoretical ideas of galaxy formation (Mo et al 1998), but agrees with recent numerical works of more massive galaxies (Desmond et al 2017;Garrison-Kimmel et al 2018;Jiang et al 2019). At a fixed halo size, the weak correlation of galaxy sizes with halo spin and concentration agree with FIRE-2 zoom simulations (Garrison-Kimmel et al 2018) and semi-empirical models (Zanisi et al 2020(Zanisi et al , 2021a of more massive, rotationally supported galaxies.…”
Section: Discussionsupporting
confidence: 88%
“…Recent simulations provide a deeper understanding of, and challenge long-standing assumptions about, galaxy formation and evolution. Perhaps contrary to the expectation based on specific angular momentum conservation (Fall & Efstathiou 1980;Mo et al 1998), Desmond et al (2017) find in the EAGLE simulation that at a fixed stellar mass, the galaxy size weakly correlates with halo mass, concentration or spin. On top of that, Somerville et al (2018) conclude from their sample of Galaxy And Mass Assembly (GAMA) and the Cosmic Assembly Near Infrared Deep Extragalactic Legacy (CANDELS) surveys mapped to the Bolshoi-Planck dissipationless 𝑁−body simulation that the ratio of galaxy to halo size decreases slightly with cosmic time for less massive galaxies, while the ratio of galaxy size to halo size times halo spin -𝑅 1/2 /(𝑅 vir 𝜆) -is lower for more massive galaxies below 𝑧 3.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Crain et al (2015) found that galaxy sizes can serve as important constraints on feedback models, Ferrero et al (2017) showed that realistic sizes and their evolution are crucial for reproducing the Tully-Fisher relation and its evolution, and Desmond et al (2016) found that galaxy sizes depend very weakly on halo properties, at a given stellar mass. Furlong et al (2017), separating active and quenched galaxies, found a good match between the sizes of EAGLE galaxies and observed ones.…”
Section: Introductionmentioning
confidence: 99%
“…Some works also highlighted a further correlation between the size of a galaxy, , and that of its host dark matter halo, ℎ (e.g. Fall 1983;Mo et al 1998;Kravtsov 2013;Huang et al 2017;Desmond 2017;Hearin et al 2019;Desmond et al 2018;Somerville et al 2018;Lapi et al 2018b;Mowla et al 2019;Zanisi et al 2020, but see also Desmond et al 2017 ). When coupled together in a semi-empirical model, the SMHM and − ℎ relations become powerful tools to simultaneously probe the mass and structural evolution of galaxies in a full cosmological context.…”
Section: Introductionmentioning
confidence: 99%